2022
DOI: 10.3889/oamjms.2022.8476
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor, Epidermal Growth Factor, and Epithelialization Analysis on Full-Thickness Wound Applied with Topical Erythropoietin

Abstract: BACKGROUND: Skin wounds are a major challenge, such as full-thickness wounds that need a long time to heal. However, the addition of erythropoietin can accelerate the wound healing process. AIM: This study was aimed to determine the effect of topical erythropoietin administration on vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), and epithelialization in the wound healing process. METHODS: This was randomized controlled trial. Full-thickness wounds were created on the back of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Administration of recombinant human EPO (rhEPO) has been shown to be helpful in the lessening of in ammation and initiation of the healing progression in an extensive diversity of preclinical models as well as in patients [51]. Regarding diabetes, reports have shown that rhEPO can advance the diabetic status in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of recombinant human EPO (rhEPO) has been shown to be helpful in the lessening of in ammation and initiation of the healing progression in an extensive diversity of preclinical models as well as in patients [51]. Regarding diabetes, reports have shown that rhEPO can advance the diabetic status in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Gregory et al (2002), propolis in the form of skin cream when compared to silver sulfadiazine (AgSD) promoted faster re-epithelialization, hence faster wound healing, and showed consistently lower levels of inflammation and a more rapid cicatrization. A study by Bastari et al (2023) showed that re-epithelization by propolis extract showed a more prominent epithelial thickness compared to re-epithelialization by control treatment. Another study showed that the healing efficacy of propolis derived from Nigerian bees on fullthickness skin lesions in rats was enhanced, indicating its potential as a therapeutic agent for various types of wounds in both fauna and humans (Eyarefe et al, 2019).…”
Section: Promotion Of Epithelialization and Reepithelializationmentioning
confidence: 99%